Large-scale phenotypic and genomic analysis of Listeria monocytogenes reveals diversity in the sensitivity to quaternary ammonium compounds but not to peracetic acid - Ivanova, Mirena; Laage Kragh, Martin; Szarvas, Judit; Tosun, Elif Seyda; Holmud, Natacha Friis; Gmeiner, Alexander; Amar, Corinne; Guldimann, Claudia; Huynh, TuAnh N; Karpíšková, Renáta; Rota, Carmen; Gomez, Diego; et al. (Applied and environmental microbiology, 2025)
UNLABELLED: Listeria monocytogenes presents a significant concern for the food industry due to its ability to persist in the food processing environment. One of the factors contributing to its persistence is decreased sensitivity to disinfectants. Our objective was to assess the diversity of L. monocytogenes sensitivity to food industry disinfectants by testing the response of 1,671 L. monocytogenes isolates to quaternary ammonium compounds (QACs) and 414 isolates to peracetic acid (PAA) using broth microdilution and growth curve analysis assays, respectively, and to categorize the isolates into sensitive and tolerant. A high phenotype-genotype concordance (95%) regarding tolerance to QACs was obtained by screening the genomes for the presence of QAC tolerance-associated genes bcrABC, emrE, emrC, and qacH. Based on this high concordance, we assessed the QAC genes' dissemination among publicly available L. monocytogenes genomes (n = 39,196). Overall, QAC genes were found in 23% and 28% of the L. monocytogenes collection in this study and in the global data set, respectively. bcrABC and qacH were the most prevalent genes, with bcrABC being the most detected QAC gene in the USA, while qacH dominated in Europe. No significant differences (P > 0.05) in the PAA tolerance were detected among isolates belonging to different lineages, serogroups, clonal complexes, or isolation sources, highlighting limited variation in the L. monocytogenes sensitivity to this disinfectant. The present work represents the largest testing of L. monocytogenes sensitivity to important food industry disinfectants at the phenotypic and genomic level, revealing diversity in the tolerance to QACs while all isolates showed similar sensitivity to PAA. IMPORTANCE: Contamination of Listeria monocytogenes within food processing environments is of great concern to the food industry due to challenges in eradicating the isolates once they become established and persistent in the environment. Genetic markers associated with increased tolerance to certain disinfectants have been identified, which alongside other biotic and abiotic factors can favor the persistence of L. monocytogenes in the food production environment. By employing a comprehensive large-scale phenotypic testing and genomic analysis, this study significantly enhances the understanding of the L. monocytogenes tolerance to quaternary ammonium compounds (QACs) and the genetic determinants associated with the increased tolerance. We provide a global overview of the QAC genes prevalence among public L. monocytogenes sequences and their distribution among clonal complexes, isolation sources, and geographical locations. Additionally, our comprehensive screening of the peracetic acid (PAA) sensitivity shows that this disinfectant can be used in the food industry as the lack of variation in sensitivity indicates reliable effect and no apparent possibility for the emergence of tolerance.
Keywords: Microbial Sensitivity Tests; genom bakteriální; dezinficiencia; disinfectants; peracetic acid; kyselina peroctová; genomika; mikrobiální testy citlivosti; Phenotype; Listeria monocytogenes; quaternary ammonium compounds; food industry; bakteriální proteiny; Food Microbiology; Disinfectants; Drug Resistance, Bacterial; fenotyp; kvartérní amoniové sloučeniny; Bacterial Proteins; Quaternary Ammonium Compounds; bakteriální léková rezistence; Genome, Bacterial; Peracetic Acid; Genomics; potravinářská mikrobiologie